Education data for decision making (EDDATA II): key achievements and lessons learned; final report | UNESCO IIEP Learning Portal - Mulcahy-Dunn, Amy; Dick, Anna; Crouch, Luis; Newton, Erin (USAID; RTI International, 2016)
USAID's Education Data for Decision Making (EdData II) was implemented over a 12 year period beginning in 2004. EdData II had at its core the goal of improving access to data for USAID Missions and host country ministries, to use for making informed policy decisions. The tools and research developed under EdData II whelped to inform the development of learning metrics under the Sustainable Development Goals (2015); provide evidence to support the design and monitor the implementation of USAID's 2011-2017 Education strategy, and provide actionable, high-quality data to inform policy and practice in around 35 countries. The report reflects on EdData II and the project's impact, providing a summary of the most salient and impactful project activities, and drawing key lessons from their development and implementation. [...] The report is divided into four sections, as follows. Sections 1 and 2 begin with an overview of the background and key accomplishments of the EdData II contract and objectives, followed by a synopsis of EdData II task orders and their scope. Section 3, the main body of the report, delineates the key technical achievements of the program, including data collection tools, analysis, and measurement; pilot intervention programs; original and secondary research; and dissemination activities, as well as the implications of each. Section 4 reflects on the lessons learned from this work. In addition, several annexes provide further details about various aspects of the program.

Personal Data Broker: A Solution to Assure Data Privacy in EdTech - Amo, Daniel; Fonseca, David; Alier, Marc; García-Peñalvo, Francisco José; Casañ, María José; Alsina, María (Springer International Publishing, 2019)
Educational technologies (Edtech) collect private and personal data from students. This is a growing trend in both new and already available Edtech. There are different stakeholders in the analysis of the collected students’ data. Teachers use educational analytics to enhance the learning environment, principals use academic analytics for decision making in the leadership of the educational institution and Edtech providers uses students’ data interactions to improve their services and tools. There are some issues in this new context. Edtech have been feeding their analytical algorithms from student’s data, both private and personal, even from minors. This draws a critical problem about data privacy fragility in Edtech. Moreover, this is a sensitive issue that generates fears and angst in the use of educational data analytics in Edtech, such as learning management systems (LMS). Current laws, regulations, policies, principles and good practices are not enough to prevent private data leakage, security breaches, misuses or trading. For instance, data privacy agreements in LMS are deterrent but not an ultimate solution due do not act in real time. There is a need for automated real-time law enforcement to avoid the fragility of data privacy. In this work, we take a step further in the automation of data privacy agreement in LMS. We expose which technology and architecture are suitable for data privacy agreement automation, a partial implementation of the design in Moodle and ongoing work.
Keywords: Academic analytics; Blockchain; Data privacy; Digital identity; Educational data mining; Learning Analytics; Moodle; Smart contracts

Meeting the data challenge in education: A knowledge and innovation exchange - Crouch, Luis (Global Partnership for Education, 2019)
The purpose of this paper is to describe the current landscape in education data systems and spark discussion and debate around potential areas for KIX investment.
Keywords: ___working_potential_duplicate

Leveraging data in African countries: Curating government microdata for research - Woolfrey, Lynn (DataFirst Technical Papers, 2013)
Governments mandate their National Statistics Offices to collect empirical data through censuses and surveys to determine appropriate national policies. Further investigation of this data by academics can help evaluate the effectiveness of government action. In many countries governments have created policies and institutions to share official data with researchers to allow independent evaluation of both the data and the policies informed by the data. In 2009 a survey was undertaken to assess ease of access to government survey microdata in African countries. This investigation revealed that the sharing of African government microdata is constrained by several obstacles. African National Statistics Offices, the main African data producers, have limited resources to curate microdata and ensure its long-term availability. Consequently many African data producers do not follow international best practice with regard to survey data management or make the microdata from official surveys available for research purposes. A further obstacle in Africa is inadequate producer-user communication channels. Concerns around the confidentiality of respondent information also present a barrier to data usage for research, as does the bureaucratic nature of government institutions involved in data production. A follow-up survey undertaken in 2012 examined improvements in data access and other dimensions of data quality in the intervening years, focusing on Statistics Offices participating in a donor project to advance data curation in resource poor countries. The survey showed that the provision of appropriate data curation tools can improve data sharing for policy feedback. However, this is more effective in countries with sound data usage policies driven by African decision-makers who appreciate the role of data utilisation in national development.

Can cost-effectiveness analysis integrate concerns for equity? Systematic review - Johri, Mira; Norheim, Ole Frithjof (International Journal of Technology Assessment in Health Care, 2012)
OBJECTIVES: The aim of this study was to promote approaches to health technology assessment (HTA) that are both evidence-based and values-based. We conducted a systematic review of published studies describing formal methods to consider equity in the context of cost-effectiveness analysis (CEA). METHODS: Candidate studies were identified through an unrestricted search of the Pub Med and EMBASE databases. The search closed on January 20, 2011. We identified additional studies by consulting experts and checking article bibliographies. Two authors independently reviewed each candidate study to determine inclusion and extracted data from studies retained for review. In addition to documenting methods, data extraction identified implicit and explicit notions of fairness. Data were synthesized in narrative form. Study quality was not assessed. RESULTS: Of the 695 candidate articles, 51 were retained for review. We identified three broad methods to facilitate quantitative consideration of equity concerns in economic evaluation: integration of distributional concerns through equity weights and social welfare functions, exploration of the opportunity costs of alternative policy options through mathematical programming, and multi-criteria decision analysis. CONCLUSIONS: Several viable techniques to integrate equity concerns within CEA now exist, ranging from descriptive approaches to the quantitative methods studied in this review. Two obstacles at the normative level have impeded their use in decision making to date: the multiplicity of concepts and values discussed under the rubric of equity, and the lack of a widely accepted normative source on which to ground controversial value choices. Clarification of equity concepts and attention to procedural fairness may strengthen use of these techniques in HTA decision making.
Keywords: Canada; Cost-Benefit Analysis; Decision Support Techniques; Health Resources; Health Services Accessibility; Health Status Disparities; Humans; Quality-Adjusted Life Years; Social Justice; Social Welfare

Analyzing and Utilizing Assessment Data for Better Learning Outcomes - UNESCO (2017)

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1)   Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Using video for professional development: the role of the discussion facilitator - Coles, Alf (Journal of Mathematics Teacher Education, 2013)
Past research into the use of video for professional development has failed to problematise or theorise sufﬁciently the role of the discussion facilitator. It has been reported consistently that it can be hard or take time to establish norms for discussion of video but little has been said about reasons why, or the role of the discussion facilitator. As a starting point in this area, I suggest ﬁves aspects or decision points in the role of the facilitator. Two aspects are taken from the literature and the others are drawn from empirical data, collected as part of an enactivist study into the use of video in one secondary school. At the school, teachers commented on ﬁnding video watching in a group more useful than lesson observation, with no evidence of this taking time to develop. I offer speculations, based on enactivist category theory, as to why the use of video in this school is effective. Having presented key aspects of the role of the facilitator of video use, a further look at the detail of the data from discussions serves to highlight some of the complexities involved in just one of the categories (and, by implication, the others). I conclude that the role of the facilitator cannot be separated from a consideration of the historical context in which discussion takes place.

Education data for decision making (EDDATA II): key achievements and lessons learned - USAID (Unesco IIEP Learning Portal, 2016)

Education Data for Decision Making (EDDATA II): Key achievements and lessons learned: Final report - USAID (USAID, 2016)

Digital School Census in 10 Weeks? How it was done in Sierra Leone - Namit, Kariba; Mai, Thanh Thi (World Bank Blogs, 2019)
Note: This blog is specifically about Sierra Leone’s successful transition to a digital school census but has broader implications for other countries who plan to adopt digital tools at a wider scale to collect data and monitor education and healthcare facilities in their countries. In April of last year, the new Minister of Finance of Sierra Leone approached the World Bank with a strong commitment to prioritize education and an intriguing request.

Literature Reviews of Educational Technology Research in Low- and Middle-Income Countries: An audit of the field - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
Keywords: LP: English; R:Literature review, systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode; educational technology, EdTech, low-income countries, literature review

Teaching with the Test: Experimental Evidence on Diagnostic Feedback and Capacity Building for Public Schools in Argentina - de Hoyos, Rafael; Ganimian, Alejandro J; Holland, Peter A (World Bank, 2017)

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Focus Group Interviewing - Krueger, Richard A.; Casey, Mary Anne (Handbook of Practical Program Evaluation, 2015)
This chapter discusses using focus groups as a component of an evaluation strategy. It focuses on both the benefits and the limitations of using this method and also offers suggestions for the effective use of focus group interviewing in an evaluation. Focus groups are a wonderful method for gathering information for formative and summative evaluations. A key role is the study team leader, sometimes called the principal investigator (PI), who takes on the overall leadership of the study. Team members work together to complete the study, but individuals take primary responsibility for certain tasks. The chapter describes these tasks and roles. Successful focus group studies are grounded on five key steps: planning, developing questions, recruiting, moderating, and analyzing. Each of these steps is critical to success. Those who seek to have successful focus groups should be attentive to performing each step with care, thought, and skill.
Keywords: classic analysis strategy; focus group interviewing; focus group recruitment; formative evaluations; study team leader; summative evaluations

Conducting Semi-Structured Interviews - Adams, William C. (Handbook of Practical Program Evaluation, 2015)
Conducted conversationally with one respondent at a time, the semi-structured interview (SSI) employs a blend of closed- and open-ended questions, often accompanied by follow-up why or how questions. About one hour is considered a reasonable maximum length for SSIs in order to minimize fatigue for both interviewer and respondent. This chapter begins with a discussion on the disadvantages and advantages of SSIs. Despite the disadvantages and costs of SSIs, they offer some extraordinary benefits as well. Semi-structured interviews are superbly suited for a number of valuable tasks, particularly when more than a few of the open-ended questions require follow-up queries. The chapter presents some recommendations that can be considered when constructing an SSI guide. All in all, effectively conducted semi-structured interviews, even though labor intensive, should be worth the effort in terms of the insights and information gained.
Keywords: SSI guide; open-ended questions; semi-structured interviews

What Matters Most for Education Management Information Systems: A Framework Paper - Abdul-Hamid, Husein (SABER Working Paper Series, 2014)
Keywords: Academic Assessments; Access to Data; Access to Education; Access to Information; Adult Education; Annual School Census; Application Programming; Assessment Framework; Average Teacher Salaries; Basic Education; Basic Education Statistics; Best Practice; Business Intelligence; Care Providers; Class Sizes; Classroom; Classroom Learning; Classrooms; Client Countries; Communication Technology; Communications Technologies; Communications Technology; Completion Rates; Continuing Education; Curriculum; Data Analysis; Data Collection; Data Coverage; Data Gathering; Data Providers; Data Sharing; Data Sources; Data Systems; Data Warehouse; Decision Makers; Decision Making; Decision-Making; Demand for Education; Domain; Domains; Early Childhood; Early Childhood Development; Early Childhood Education; Educated Population; Education Budget; Education Data; Education Development; Education Institutions; Education Management; Education Management Systems; Education Outcomes; Education Planning; Education Policies; Education Policy; Education Providers; Education Services; Education Statistics; Education Strategy; Education System; Education Systems; Education Targets; Education Teachers; Education for All; Educational Development; Educational Expenditures; Educational Inputs; Educational Outcomes; Educational Planning; Educational Processes; Educational Quality; Educational Sciences; Educators; Enabling Environment; Enrollment Data; Enrollment Levels; Enrollment Rates; Enrollment Statistics; Equitable Education; Expert Opinion; Female Teachers; Financial Performance; Formal Education; Functionalities; Functionality; Gender Equality; Gender Equity; Gender Parity; Gender Parity Index; Girls; Global Education; Gross Enrollment; Gross Enrollment Ratio; High Quality Education; Human Resources; Improvement of Education; Information Gaps; Information System; Information Systems; Information Technology; Innovation

The (Perceived) Returns to Education and the Demand for Schooling - Jensen, Robert (The Quarterly Journal of Economics, 2010)
Economists emphasize the link between market returns to education and investments in schooling. Though many studies estimate these returns with earnings data, it is the perceived returns that affect schooling decisions, and these perceptions may be inaccurate. Using survey data for eighth-grade boys in the Dominican Republic, we find that the perceived returns to secondary school are extremely low, despite high measured returns. Students at randomly selected schools given information on the higher measured returns completed on average 0.20–0.35 more years of school over the next four years than those who were not.

Sierra Leone’s Medium-Term National Development Plan 2019-2023: Education for Development. - Government of Sierra Leone (2019)

The EdTech Hub’s approach to amplifying impact through engagement – The EdTech Hub - Jamieson Eberhardt, Molly (EdTech Hub, 2019)
If you have spent time working in the education sector, you’ll know that even marginal gains are worthy of celebration. Those of us involved in launching the EdTech Hub know this well — from our experience as teachers, researchers, advisers, programme implementers, and civil servants. Nevertheless, we have the ambition to help accelerate progress toward quality education at an unprecedented rate. We of course know that sustainable change often takes time, and we respect hard-earned marginal gains. But what we’re really after is improvement in education outcomes at a pace that matches the urgency of the problem — think millions of children receiving quality education within a decade, not in decades.
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Cost-Effectiveness and Affordability of Interventions, Policies, and Platforms for the Prevention and Treatment of Mental, Neurological, and Substance Use Disorders - Levin, Carol; Chisholm, Dan (Mental, Neurological, and Substance Use Disorders: Disease Control Priorities, 2016)
Since the turn of the millennium, considerable progress has been made in developing an evidence base on which interventions are effective and feasible for improving mental health in low- and middle-income countries (LMICs). Such evidence provides a critical input to the formulation of plans and priorities to address the large and growing burden of mental, neurological, and substance use (MNS) disorders. However, for successful and sustainable scale-up of effective interventions and innovative service delivery strategies, decision makers require not only evidence of an intervention’s impact on health and other outcomes, such as equity or poverty, but also evidence of its cost and cost-effectiveness. Cost data provide information relevant to the financial planning and implementation of prioritized, evidence-based strategies; cost-effectiveness analysis indicates the relative efficiency or value for money associated with interventions or innovations. The application of economic evaluation to MNS disorders has largely focused on the assessment of a specific intervention’s costs and health outcomes, relative to some comparator, which may be treatment as usual, another innovation, or no intervention. Such assessments have often been conducted alongside clinical trials, enabling health economic researchers to add resource use questions to study protocols, generate estimates of each trial participant’s health care costs, and relate these costs to primary outcome measures in the form of cost-effectiveness ratios. We review this type of economic evidence over the course of this chapter, with a particular focus on studies that have been successfully carried out in LMICs. However, the number of completed studies remains small and insufficient to inform resource allocation decisions in all the national settings where cost-effectiveness information would be valuable, including the many countries where informal or traditional health care represents the predominant model of service availability. This paucity of economic evidence reflects the overall lack of resources and infrastructure for mental health services in LMICs, including research capacity. Partly to address the paucity of cost-effectiveness trials, as well as their intrinsic specificity to the setting in which they are conducted, a broader, modeling-based approach has also been used to build up economic evidence for international mental health policy and planning. This approach includes the earlier editions of the Disease Control Priorities (DCP) project and the World Health Organization’s (WHO) CHOosing Interventions that are Cost-Effective (CHOICE) project. Such model-based studies rely on existing data, as well as several analytical assumptions; these studies have adopted an epidemiological, population-based approach that identifies the expected costs and health impacts of delivering evidence-based interventions at scale in the population as a whole, whether a specific country or an entire region. We also review this form of economic evidence and comment on important gaps in the current evidence base, as well as the relative strengths and limitations of this approach. One important limitation of conventional cost-effectiveness analysis—whether garnered through trial-based or model-based approaches—is that it is restricted to consideration of the specific implementation costs and health-related outcomes of an intervention; it does not typically extend to the nonhealth or wider economic or social value of investing in mental health innovation and service scale-up. In particular, cost-effectiveness analysis in its conventional form has little to say about the equitable distribution of costs and health gains across different groups of the target population. Incorporation of such concerns into economic evaluation represents a major objective of extended cost-effectiveness analysis, which is explored and addressed specifically in chapter 13 in this volume (Chisholm, Johansson, and others 2015). In this chapter, we review the available cost-effectiveness evidence for the different levels and underpinning strategies of the mental health care system, with a focus on information generated in or for LMICs. Based on the overall analytical framework and priority intervention matrices developed for this volume, the remainder of the chapter is presented as follows. First, we consider the economic evidence for mental health prevention and protection at the population and community levels of the health and welfare system, including legislative, regulatory, and informational measures at the public policy level (population platform), as well as school-, workplace-, and community-based programs (community platform). We then examine the economic evidence relating to the identification and treatment of MNS disorders (health care platform), focusing on the relative cost-effectiveness or efficiency of treatment programs implemented in nonspecialized versus more specialized health care settings. Finally, we assess the financial costs and budgetary implications of implementing or scaling up a set of prioritized, cost-effective interventions. Our review is based on available, published literature. A systematic search of the literature for LMICs was undertaken in PubMed to find articles published since 2000 in English. The search combined terms for specific mental health interventions with economic terms such as “cost,” “cost-effectiveness,” or “quality-adjusted life year (QALY),” as well as the names of all LMICs and their respective regions (see annex 12A for a list of search terms used to identify relevant literature). Where little or no literature was found for LMICs on interventions of potential importance, this systematic search was augmented by selective searches of the literature available since 1995 for high-income countries (HICs); however, these results are not included in the figures or tables. Annex 12B provides the search statistics. Articles included in the review were graded using the checklist of Drummond and others (2005) to generate a quality score for each article, with most studies graded between 7 and 10. Annex 12C provides a list of studies that were used to generate the tables and figures presented in this chapter. It presents detailed information on the intervention characteristics and comparators, target population group, geographic location, methodology, results, and quality scores. All cost-effectiveness results are presented in 2012 US$ except where noted otherwise. Consistent with earlier iterations of DCP, reported regional estimates refer to the World Bank’s categorization of countries by income.

“Matching Person & Technology (MPT) Model” for Technology Selection as Well as Determination of Usability and Benefit from Use - Martinez, A. P.; Scherer, M. J. (Living in the State of Stuck, 2018)
Technologies have become smarter, smaller, more portable or wearable, and more adaptable. This has led to more choice and, in many cases, complexity in decision-making about selecting the best device and features for a given user. A good match of person and technology requires attention to (a) aspects of and resources in the environments in which the technology will be used, (b) the needs, expectations and preferences of the user, and (c) the functions and features of the technology and service delivery process. If the match is not a quality one from the standpoint of the end user, and the user experience (UX) is not satisfactory, then the technology may go unused, or may not be used optimally. There is a need for an improved person-AT matching and outcomes assessment process because studies and reports show in general that there is a high level of dissatisfaction and nonuse or discard of technology by consumers. Psychologists are uniquely qualified to partner with technology developers in implementing an assessment process that inquires into the potential technology user's predisposition to use a particular technology by addressing, subjective view of current capabilities, view of achievements as well as needs in key life domains of activities and participation, and ratings of fundamental personal factors such as mood status, support from others, engagement in therapy activities and desire to use technology. Utilization of the MPT model and accompanying assessment process has been proven to result in enhanced technology use and goal achievement. Research increasingly highlights the fact that consumers are less likely to use recommended devices when their needs are neither fully addressed nor understood during the technology selection process. A user's perspective of their needs and preferences may be obtained by having them identify and prioritize their desired outcomes and then rate progress in achieving them. This approach was used in developing the Matching Person and Technology measures and has also been used in developing Such a person-centered approach allows outcomes to be measured in reference to changes in a person's satisfaction in achieving desired goals, not merely their functional ability to achieve them. An idiographic evaluation is used (i.e., the person is the unit of analysis and serves as his or her own control), not a normative one (i.e., the person is compared to his or her peers). An idiographic evaluation best captures a consumer-directed and social model perspective of outcomes assessment. Many studies have examined the psychometric qualities and usefulness of the Matching Person and Technology measures. Below is the most recent data on one MPT measure, the Assistive Technology Device Predisposition Assessment (ATD PA), from a study done in the country Greece (Koumpouros et al. 2017; n=115).  Excellent interrater reliability (ICC=0.981, ranging from 0.973-0.987)  Adequate internal consistency (Cronbach's alpha =0.701, ranging from 0.605-0.701)  Adequate-Excellent construct validity for items in the Adaptablility subscale (r=0.537 to 0.783)  Excellent construct validity for items in the Fit to Use subscale (r= 0.691 to 0.801)  Adequate-Excellent construct validity for items in the Socializing (r= 0.498 to 0.767)  Low correlation coefficients between each subscale, indicating subscales measure unique constructs Improvements in person-centered assistive technology services and outcomes assessment are needed, given reports of a high level of dissatisfaction and nonuse of technology by consumers. It is important to ensure an evidence-based, client-centered assessment for determining the match of individuals with the most appropriate technologies for their use. Achieving a desired outcome begins at the point of technology consideration and then progresses to product selection. ABSTRACT Cognitive impairment often results in a range of functional and lifestyle changes for many individuals. This article discusses the development and evolution of a multidisciplinary model of cognitive rehabilitation outpatient practice that integrates technology to improve patient outcomes. The described interdisciplinary treatment approach highlights the need for collaboration by treating providers; focuses on the individual being an active participant in treatment; and discusses the value that assistive technology can bring to cognitive rehabilitation work as it relates to patient success, functional improvement, and implementation of appropriate and patient specific technological strategies.

Design-based online teacher professional development to introduce integration of STEM in Pakistan - Anwar, Tasneem (University of Minnesota, 2017)
In today's global society where innovations spread rapidly, the escalating focus on science, technology, engineering and mathematics (STEM) has quickly intensified in the United States, East Asia and much of Western Europe. Our ever-changing, increasingly global society faces many multidisciplinary problems, and many of the solutions require the integration of multiple science, technology, engineering, and mathematics (STEM) concepts. Thus, there is a critical need to explore the integration of STEM subjects in international education contexts. This dissertation study examined the exploration of integration of STEM in the unique context of Pakistan. This study used three-phase design-based methodological framework derived from McKenney and Reeves (2012) to explore the development of a STEM focused online teacher professional development (oTPD-STEM) and to identify the design features that facilitate teacher learning. The oTPD-STEM program was designed to facilitate eight Pakistani elementary school teachers' exploration of the new idea of STEM integration through both practical and theoretical considerations. This design-based study employed inductive analysis (Strauss and Corbin, 1998) to analyze multiple data sources of interviews, STEM perception responses, reflective learning team conversations, pre-post surveys and artifacts produced in oTPD-STEM. Findings of this study are presented as: (1) design-based decisions for oTPD-STEM, and (2) evolution in understanding of STEM by sharing participant teachers' STEM model for Pakistani context. This study advocates for the potential of school-wide oTPD for interdisciplinary collaboration through support for learner-centered practices. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
Keywords: 0530:Teacher education; 0714:Science education; Attitude Measures; Community of practice; Design; Design-based research; ERIC, Resources in Education (RIE); Education; Educational Technology; Elementary Education; Elementary School Teachers; Faculty Development; Foreign Countries; Interdisciplinary Approach; Interviews; Models; Online Courses; Online teacher professional development; Pakistan; Reflective practices; STEM Education; Science education; Stem integration; Student Centered Learning; Teacher Attitudes; Teacher education; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2096054; __finaldtb

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets

GIS in Education Planning: The Kenyan School Mapping Project - Mulaku, G.C.; Nyadimo, E. (Survey Review, 2011)
School mapping consists of the building of geospatial databases of educational, demographic and socioeconomic data for educational institutions in order to support educational planning and decision making. Such databases contain data such as the geographic location of schools, the numbers of existing schools of different levels in the public and private sectors, their capacities, physical condition and facilities, enrolment and the number of teachers and their attributes. Also often included are data on related natural features and infrastructure such as rivers, roads, economic and administrative centers, medical facilities, religious facilities, etc. This paper describes the Kenyan School Mapping Project, whose objective was to collect such data for all Kenyan learning institutions and to integrate them in a GIS database that could be queried to provide useful information for educational planners, other professional users and average citizens. Results show that at the time of the project, there were nearly 73000 learning institutions in Kenya, ranging from early childhood schools to universities; useful information products on important educational indicators such as schools distribution, enrolments, pupil-teacher ratios and gender parity indices have also been generated from GIS analysis of the data. These results have demonstrated the utility of the database for its stated purpose and therefore shown the project to be a useful model that can be emulated by other developing countries.
Keywords: EMIS; GIS; KENYA; SCHOOL MAPPING

Baseline-Endline Report: Reaching the Unreached (RtU) through Open and Distance Learning (ODL) in Bangladesh, India and Pakistan - Ferreira, Frances; Cruz, Charisse; Smith, Kristina; Commonwealth of Learning (COL) (British Columbia) (Commonwealth of Learning, 2018)
This report documents the baseline-endline study by the GIRLS Inspire team's Reaching the Unreached project to examine the implications of skills training and education for women's and girls' empowerment and sustainable livelihoods in Bangladesh, India and Pakistan. It is based on data collected from quarterly reports mirrored against the project outcomes, meeting reports and surveys from March 2016 to March 2017. The quarterly and meeting reports documented the activities undertaken to provide training for unreached women and girls in the selected countries. While the actual training was offered exclusively to women and girls, the reports and surveys also captured the input of men and boys in terms of their participation in various community events and as staff members of the partner organisations.
Keywords: Access to Education; Bangladesh; Barriers; Child Abuse; Decision Making; Distance Education; Dropouts; Economic Factors; Educational Attainment; Elementary Secondary Education; Employer Attitudes; Employment; Empowerment; Females; Foreign Countries; Health; Income; India; Job Skills; Marriage; Occupational Aspiration; Pakistan; Postsecondary Education; Program Effectiveness; Skill Development; Sustainability; Training; Womens Education

Handbook on impact evaluation: quantitative methods and practices - Khandker, Shahidur R.; Koolwal, Gayatri B.; Samad, Hussain A. (World Bank, 2010)
This book reviews quantitative methods and models of impact evaluation. The formal literature on impact evaluation methods and practices is large, with a few useful overviews. Yet there is a need to put the theory into practice in a hands-on fashion for practitioners. This book also details challenges and goals in other realms of evaluation, including monitoring and evaluation (M&E), operational evaluation, and mixed-methods approaches combining quantitative and qualitative analyses. This book is organized as follows. Chapter two reviews the basic issues pertaining to an evaluation of an intervention to reach certain targets and goals. It distinguishes impact evaluation from related concepts such as M&E, operational evaluation, qualitative versus quantitative evaluation, and ex-ante versus ex post impact evaluation. Chapter three focuses on the experimental design of an impact evaluation, discussing its strengths and shortcomings. Various non-experimental methods exist as well, each of which are discussed in turn through chapters four to seven. Chapter four examines matching methods, including the propensity score matching technique. Chapter five deal with double-difference methods in the context of panel data, which relax some of the assumptions on the potential sources of selection bias. Chapter six reviews the instrumental variable method, which further relaxes assumptions on self-selection. Chapter seven examines regression discontinuity and pipeline methods, which exploit the design of the program itself as potential sources of identification of program impacts. Specifically, chapter eight presents a discussion of how distributional impacts of programs can be measured, including new techniques related to quantile regression. Chapter nine discusses structural approaches to program evaluation, including economic models that can lay the groundwork for estimating direct and indirect effects of a program. Finally, chapter ten discusses the strengths and weaknesses of experimental and non-experimental methods and also highlights the usefulness of impact evaluation tools in policy making.
Keywords: Accountability; Audits; Beneficiaries; Capacity Building; Clinics; Community Development; Community Participation; Comparison Groups; Control Groups; Counterfactual; Counterfactuals; Data Analysis; Data Collection; Decision Making; Development Research; Economic Factors; Evaluation Design; Evaluation Methods; Evaluation Studies; Evaluators; Ex Ante Analysis; Ex Post Evaluation; Ex Post Impact Evaluation; Exercises; Experimental Data; Experimental Design; Families; Final Indicators; Financial Support; Flexibility; General Practice; Gross Domestic Product; Household Income; Hygiene; Impact Assessment; Impact Evaluation; Impact Evaluation Tools; Impact Indicators; Income; Inequality; Instrumental Variables; Intermediate Indicators; Intermediate Outcomes; Intervention; Interviews; Labor Markets; Learning; M&e Systems; Matching Methods; Methodologies; Microdata Set; Modeling; Mortality; Nonexperimental Methods; Nongovernmental Organizations; Nonparticipant Groups; Nutrition; Performance Indicators; Policy Changes; Pollution; Poverty Alleviation; Poverty Impacts; Poverty Reduction; Poverty Reduction Programs; Program Beneficiaries; Program Effectiveness; Program Effects; Program Evaluation; Program Impacts; Program Implementation; Program Interventions; Program Outcomes; Programs; Project Management; Project Monitoring; Project Objectives; Propensity Score Matching; Qualitative Analysis; Qualitative Data; Qualitative Methods; Quantitative Data; Quantitative Evaluation; Quantitative Methods; Quantitative Research; Questionnaires; Reducing Poverty; Reflexive Comparisons; Reliability; Research Projects; Researchers; Secondary Schools; Selection Bias; Service Delivery; Simulation; Simulations; Social Networks; Survey Data; Survey Instruments; Targeting; Techniques

The evaluation of "technological pedagogical content knowledge based argumentation practices" training for science teachers - Çoban, Gül Ünal; Akpinar, Ercan; Baran, Bahar; Saglam, Merve Kocagül; Özcan, Erkan; Kahyaoglu, Yasemin (Egitim ve Bilim, 2016)
In science education, creating learning environments supported with technology and students' use of theory-evidence coordination when expressing their ideas is emphasized regarding the development of students' scientific reasoning, critical thinking, decision making skills, and etc. In this process, great responsibilities are fallen to teachers as planner and designer of a learning environment. In this study, it is aimed to assess the training which aims the development of science teachers' technological pedagogical content knowledge (TPACK) through argumentation practices. In this context; this study evaluated the science teachers' argumentation skills, self-efficacy perceptions towards TPACK and the teachers' views about the training. 37 science teachers working at different cities in Turkey participated in the one group pre-test post-test experimental training study, which was lasted 54 hours during a week. The training is composed of both hand and minds on argumentation practices based on TPACK. The participants joined different activities such as collaborative group works, drama, modeling, thematic games, art activities, problem-based learning, field trips, observation and workshops. In the study, Argumentation Test, TPACK Self-Efficacy Belief Scale were used as data collection tools. At the end of the training written views of science teachers towards activities were taken. In the light of the findings, this training was effective on the participants' self-efficacy levels towards technological pedagogical content knowledge. Moreover, this training resulted in a positive change in the participants' views about how a statement could be accepted as an argument. However, the increase in scores of argumentation skills was not significant. Additionally almost all of the participants stated that they found the activities useful and can use in their classes. By considering these results, some suggestions were given.
Keywords: Argumentation; Education; Professional development; Science teachers; Technological pedagogical content knowledge; __:import:01; __:match:final; __:matched; __:study_id:2097466; __finaldtb

Thematic Analysis: Striving to Meet the Trustworthiness Criteria - Nowell, Lorelli S.; Norris, Jill M.; White, Deborah E.; Moules, Nancy J. (International Journal of Qualitative Methods, 2017)
As qualitative research becomes increasingly recognized and valued, it is imperative that it is conducted in a rigorous and methodical manner to yield meaningful and useful results. To be accepted as trustworthy, qualitative researchers must demonstrate that data analysis has been conducted in a precise, consistent, and exhaustive manner through recording, systematizing, and disclosing the methods of analysis with enough detail to enable the reader to determine whether the process is credible. Although there are numerous examples of how to conduct qualitative research, few sophisticated tools are available to researchers for conducting a rigorous and relevant thematic analysis. The purpose of this article is to guide researchers using thematic analysis as a research method. We offer personal insights and practical examples, while exploring issues of rigor and trustworthiness. The process of conducting a thematic analysis is illustrated through the presentation of an auditable decision trail, guiding interpreting and representing textual data. We detail our step-by-step approach to exploring the effectiveness of strategic clinical networks in Alberta, Canada, in our mixed methods case study. This article contributes a purposeful approach to thematic analysis in order to systematize and increase the traceability and verification of the analysis.

Factors affecting cloud computing adoption in the Indian school education system - Singh, Jewan; Mansotra, Vibhakar (Education and Information Technologies, 2019)
Cloud computing is becoming a leading trend worldwide, due to its enhanced reliability, scalability, flexibility, availability and processing throughput. However, the decision related to adoption of the cloud computing model is often complicated by challenges and uncertainties about the expected business value and its overall impact on the organisation. Till date, different contemporary technology acceptance theories and models have been used to test and validate adoption chances of cloud computing at organisational and individual levels. However, no experimental study has been conducted to provide a holistic evaluation of the determinants of cloud computing in the Asian world particularly in the context of the Indian school education system. Due to lack of such studies, we propose a theoretical model based on the TOE framework to explain the role of technological, organisational and environmental factors on the adoption of cloud computing in the Indian school education system. The data was collected from fifty-six 56 randomly selected secondary schools through questionnaire based survey to examine the relationship between the variables employing 5-points Likert scale. Reliability and validity measures were used to establish the quality and the usefulness of the collected data. In addition multi co-linearity test was also conducted. In order to test the research hypothesis, multiple regression analysis was conducted. The results indicate that relative advantage, compatibility, and complexity representing technological factors; top management support representing organisational factors; and competitive pressure, external expertise and attitude towards change representing environmental factors were found to have an positive and significant influence on the adoption of cloud computing services in the Indian school education system. The findings have a great significance since they can provide knowledge about cloud computing factors as well as insights and directions to the education policy planners and decision makers for successful adoption of cloud computing technology in India.

How to do (or not to do)… gender analysis in health systems research - Morgan, Rosemary; George, Asha; Ssali, Sarah; Hawkins, Kate; Molyneux, Sassy; Theobald, Sally (Health Policy and Planning, 2016)
Gender-the socially constructed roles, behaviours, activities and attributes that a given society considers appropriate for males, females and other genders-affects how people live, work and relate to each other at all levels, including in relation to the health system. Health systems research (HSR) aims to inform more strategic, effective and equitable health systems interventions, programs and policies; and the inclusion of gender analysis into HSR is a core part of that endeavour. We outline what gender analysis is and how gender analysis can be incorporated into HSR content, process and outcomes Starting with HSR content, i.e. the substantive focus of HSR, we recommend exploring whether and how gender power relations affect females and males in health systems through the use of sex disaggregated data, gender frameworks and questions. Sex disaggregation flags female-male differences or similarities that warrant further analysis; and further analysis is guided by gender frameworks and questions to understand how gender power relations are constituted and negotiated in health systems. Critical aspects of understanding gender power relations include examining who has what (access to resources); who does what (the division of labour and everyday practices); how values are defined (social norms) and who decides (rules and decision-making). Secondly, we examine gender in HSR process by reflecting on how the research process itself is imbued with power relations. We focus on data collection and analysis by reviewing who participates as respondents; when data is collected and where; who is present; who collects data and who analyses data. Thirdly, we consider gender and HSR outcomes by considering who is empowered and disempowered as a result of HSR, including the extent to which HSR outcomes progressively transform gender power relations in health systems, or at least do not further exacerbate them.
Keywords: Female; Framework; Health Services Research; Humans; Male; Power (Psychology); Sex Factors; Sexism; Social Norms; _C:Bangladesh BGD; _C:Canada CAN; _C:Finland FIN; _C:Kenya KEN; _C:Malawi MWI; _C:Mozambique MOZ; _C:Nepal NPL; _C:South Africa ZAF; _C:Uganda UGA; _C:Yemen YEM; __C:scheme:1; gender; gender analysis; health systems; health systems research

Bangladesh Education Sector Public Expenditure Review - Bhatta, Saurav Dev; Genoni, Maria Eugenia; Sharma, Uttam; Khaltarkhuu, Buyant Erdene; Maratou-Kolias, Laura; Asaduzzaman, T. M. (World Bank, 2019)
Adequate investment in human capital development is critical for enabling Bangladesh to reach its goal of becoming an upper middle-income country. Bangladesh, currently a lower-middle country with an annual per capita gross national income (GNI) of USD 1,470 (WDI 2019), aims to attain upper-middle income status by 2021 and eliminate poverty by 2030. Recognizing the importance of investing in education for building its human capital base, the government of Bangladesh (GoB) has been allocating a large portion of the national budget to the education sector each year during the past two decades. Effective utilization and equitable distribution of allocated public spending is important for ensuring adequate progress in education outcomes. This report analyzes major spending and outcomes trends in the overall education sector in recent years, with a focus on primary and secondary education. Responding to the recommendation of the 2015 Bangladesh Public Expenditure Review Update for more analytical work on public spending in different sectors, including education, the current study analyzes the trends in major education expenditures, access to education, quality of education, and disparities in education outcomes in the past two decades. It also looks at the composition of education expenditure, consistency between budget allocations and actual expenditures, equity in education spending, and potential links between spending and key educational outcomes. Because of data limitations, this report focuses mainly on primary and secondary education. It is expected that this analysis will add to the literature on investments in the Bangladesh education sector and inform discussions on identifying policy priorities and making resource allocation decisions in the sector.
Keywords: Education Budget; Education Expenditure; Education Outcomes; Equity in Education; Public Expenditure Review

Decentralisation policy and practice in Ghana: the promise and reality of community participation in education in rural communities - Essuman, Ato; Akyeampong, Kwame (Journal of Education Policy, 2011)
In 1987, the government of Ghana embarked on a process to decentralise education management to districts as part of wider social and democratic governance reforms. A central part of this reform was the prescription of active community participation in the affairs of schools within their locality. This paper explores the different meanings community participation had for school community stakeholders. It examines the multiple understandings of how community and school relations work and the factors which influence this relationship. Drawing on case study data, it argues that much of the theoretical and policy expectations on representation and participation in education by community members are only evident in form, but not as intended in practice. In poor rural contexts, it is often the local elite and relatively more educated members of the community, who become the new brokers of decision-making and, through their actions, close up the spaces for representation and participation by community members in the affairs of schools. Furthermore, the extent of community participation appears to be shaped by a ‘social contract’ based on the principle of reciprocity of roles between the community and schools, and that increasingly teachers feel accountable to the traditional hierarchical educational structure, and not to the community. The paper argues that the realisation of decentralisation policy in education has to contend with the realities of local politics of influence in the community, and tap into the positive side of this influence to improve education service delivery.
Keywords: Ghana; Parent Teacher Associations (PTA); School Management Committees (SMC); ___working_potential_duplicate; community participation; decentralisation policy